The Use of Arabic in Classes of English as a Foreign Language (EFL) - Al-Makhzoomi , Khalaf; Amin, Ahmad (Jordan Journal of Educational Sciences, 2005)
The purpose of this study was to investigate the effect of using Arabic in EFL classes. To achieve this purpose, the researchers distributed a questionnaire about the use of Arabic in EFL classes to the teachers and students of ordinary-level English at Rawdet Al-Ma’aref School in Amman, Jordan. The results of the study showed that 100% of the students and 90% of the teachers felt that Arabic should be used in their EFL classes. The respondents emphasized the fact that cultural and religious concepts should be taught by referring to Arabic in EFL classes. A noticeable percentage (85%) of students and (75%) of teachers agreed that Arabic should necessarily be used to introduce grammatical rules. The findings of the study should be taken into consideration by teachers of English as a foreign language as well as textbooks writers and curricula designers